Analisis Potensi Beberapa Sektor Ekonomi Kabupaten Nias Utara 2022 - Jalilah Ilmiha (Universitas Nusantara PGRI Kediri, 2023)
This study aims to obtain the results of an analysis of the potential of several economic sectors in North Nias Regency. From 2020, 2021, to 2022 North Nias Regency has excellent potential in the agricultural, forestry and economic sectors which have contributed to the development of Gross Regional Domestic Product (PRDB) in North Nias by 52.25% based on statistical data from Nias Regency. This is contained in the Regional Innovation Strengthening System where one of the main strategies in developing an innovation system accommodates all actors to interact with each other in order to achieve common goals in the development of a region. Based on the Joint Regulation of the Ministry of Home Affairs of the Republic of Indonesia Number 3 of 2013 and the Ministry of Research and Technology Number 36 of 2012 concerning strengthening Regional Innovation Systems. In addition, with the issuance of Government Regulation Number 38 of 2017 concerning Regional Innovation which is all forms of renewal in the administration of regional government. From the results of the GRDP (Gross Regional Domestic Product) in 2016, the GRDP at current prices for Nias Regency amounted to 2,966 billion rupiah, an increase compared to 2015, which was 2,676 billion rupiah. While the GRDP at constant prices for Nias Regency is 2,214 billion rupiahs, an increase compared to 2015, which was 2,108 billion rupiahs. The economic condition of Nias Regency showed a downward movement from 6.35 percent in 2012 to 5 percent in 2015. Where the economic conditions in Nias Regency improved slightly in 2016 as indicated by an increase in economic growth to 5.71 percent.